Inflammation-related parameter serve as prognostic biomarker in esophageal squamous cell carcinoma - Xu, Xiaoqin; Jing, Jiexian (Frontiers in Oncology, 2022)
Objective The aim of this study was to explore the predictive role of inflammation-related parameters in prognosis of esophageal squamous cell carcinoma(ESCC). Methods A total of 370 ESCC patients subjected to curative surgery were enrolled. All patients had complete medical records and did not receive preoperative adjuvant therapy. Preoperative systemic immune-inflammation index (SII) was calculated as platelet × neutrophil / lymphocyte counts, prognostic nutrition index (PNI) as albumin concentration (g/L) + 5 × total lymphocyte count (109/L), and systemic inflammation response index (SIRI) as neutrophil count × monocyte count / lymphocyte count. The optimal cut‐off values of preoperative SII, neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), PNI and SIRI were determined via receiver operating characteristic (ROC) analysis, and their correlations with clinical parameters and survival analyzed. Results NLR was associated with gender (P = 0.022), and PLR (P = 0.037), PNI (P = 0.017) was associated with survival status, LMR was related with gender (P = 0.034) and survival status (P = 0.01), SIRI was correlated with gender (P = 0.000), smoking history (P = 0.000) and drinking history (P = 0.004). Survival analysis indicated that high PLR (P = 0.042), low LMR (P = 0.001), and low PNI (P = 0.007) were predictive of poor prognosis of ESCC. Stratified analysis revealed the prognostic predictor roles of distinct markers in different ESCC subgroups. SⅡ and SIRI were predominantly correlated with the clinical outcome in the lymphatic metastasis subgroup. Further univariate analysis disclosed that T stage , smoking history, lymphatic metastasis, TNM staging, PLR, LMR and PNI potentially serve as influencing factors( P < 0.05). Multivariate analysis identified T stage (HR = 1.781, P = 0.002), TNM staging ( HR = 8.617, P = 0.001) and LMR (HR = 0.504, P = 0.001) as independent predictors for outcomes of ESCC. Conclusions Low LMR could serve as an independent marker of poor prognosis in patients with ESCC. Inflammation-related markers have distinct predictive roles in ESCC subgroups with different features.